Simple, sensitive, and cost-effective detection of wAlbB Wolbachia in Aedes mosquitoes, using loop mediated isothermal amplification combined with the electrochemical biosensing method. - Parinda Thayanukul; Benchaporn Lertanantawong; Worachart Sirawaraporn; Surat Charasmongkolcharoen; Thanyarat Chaibun; Rattanalak Jittungdee; Pattamaporn Kittayapong (Public Library of Science (PLoS), 2022)
Background Wolbachia is an endosymbiont bacterium generally found in about 40% of insects, including mosquitoes, but it is absent in Aedes aegypti which is an important vector of several arboviral diseases. The evidence that Wolbachia trans-infected Ae. aegypti mosquitoes lost their vectorial competence and became less capable of transmitting arboviruses to human hosts highlights the potential of using Wolbachia-based approaches for prevention and control of arboviral diseases. Recently, release of Wolbachia trans-infected Ae. aegypti has been deployed widely in many countries for the control of mosquito-borne viral diseases. Field surveillance and monitoring of Wolbachia presence in released mosquitoes is important for the success of these control programs. So far, a number of studies have reported the development of loop mediated isothermal amplification (LAMP) assays to detect Wolbachia in mosquitoes, but the methods still have some specificity and cost issues. Methodology/principal findings We describe here the development of a LAMP assay combined with the DNA strand displacement-based electrochemical sensor (BIOSENSOR) method to detect wAlbB Wolbachia in trans-infected Ae. aegypti. Our developed LAMP primers used a low-cost dye detecting system and 4 oligo nucleotide primers which can reduce the cost of analysis while the specificity is comparable to the previous methods. The detection capacity of our LAMP technique was 1.4 nM and the detection limit reduced to 2.2 fM when combined with the BIOSENSOR. Our study demonstrates that a BIOSENSOR can also be applied as a stand-alone method for detecting Wolbachia; and it showed high sensitivity when used with the crude DNA extracts of macerated mosquito samples without DNA purification. Conclusions/significance Our results suggest that both LAMP and BIOSENSOR, either used in combination or stand-alone, are robust and sensitive. The methods have good potential for routine detection of Wolbachia in mosquitoes during field surveillance and monitoring of Wolbachia-based release programs, especially in countries with limited resources.